2012
DOI: 10.3126/njst.v12i0.6488
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Ethnomedicinal Use, Chemical Constituents Analysis and Bioactivity Evaluation on High Altitude Medicinal Plant Delphinium brunonianum of Manang District

Abstract: The medicinal plant Delphenium brunonianum collected from Manang district, Nepal has been selected for its study on ethnomedicinal uses, phytochemical investigation and bioactivity evaluation. This plant is found to be used extensively by the community for the treatment of fever, headache, stomachache and poison removal. From phytochemical investigation, four known compounds namely ?-amyrin (1), ?-sitosterol (2), ?-sitosterol glucoside (3) and anthriscifoldine (4) have been isolated from methanol extract of D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The above spectral features are in close agreement to those observed for β-sitosterol. 9,10 Besides, a doublet at δ 4.14 (J = 6.8 Hz) integrated for one proton indicated the presence of an anomeric proton (H-1') of a glucoside moiety. The large coupling constant (6.8 Hz) of this proton demonstrated the beta (β) linkage between the aglycone and glycone moieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above spectral features are in close agreement to those observed for β-sitosterol. 9,10 Besides, a doublet at δ 4.14 (J = 6.8 Hz) integrated for one proton indicated the presence of an anomeric proton (H-1') of a glucoside moiety. The large coupling constant (6.8 Hz) of this proton demonstrated the beta (β) linkage between the aglycone and glycone moieties.…”
Section: Resultsmentioning
confidence: 99%
“…All of these data are in close agreement with the βsitosterol-3-O-β-D-glucoside. 10 Thus, compound 3 was characterized as β-sitosterol-3-O-β-D-glucoside. Its identity was also confirmed by co-TLC with authentic sample.…”
Section: Resultsmentioning
confidence: 99%
“…exhibited antibacterial properties against various bacteria like Sstaphylococcus aureus, Pseudomonas aureginous, Escherchia coli, etc. 2 However, other extracts like methylsuccimidoanthronyllycoctonine (MSAL) and the lycoctonine group of alkaloids found in Delphinium peregrinum have the toxic effect of causing neuromuscular paralysis via competitive inhibition of post-synaptic neurotransmitter acetylcholine, specifically acting at the α1 nicotinic sites in the brain and muscle, causing respiratory depression and other curare-like symptoms. 4 , 5 Other Delphinium alkaloids like methyllycaconitine (MLA), nudicauline, barbinine, deltalineetc also block neuromuscular transmission by acting as nicotinic receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…1 Their roots have been used for the treatment of fever, headache, stomachache, jaundice, and skin rashes. 2 However, some species are toxic and the toxicity of the genus Delphiniumis variable depending on growth stages and concentration of a toxic substance. 3 Poisoning usually occurs in grazing cattle and is rare in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its anti-inflammation capacity, a study by Tripathee [20] reported that the Delphinium brunoniaum extract, which is mixed in rtsa-byugs, exhibits antibacterial properties. For example, the ability to inhibit bacillus subtilis, salmonella flexinarie, pseudomonas aureginous and staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%